2015
DOI: 10.2174/1567202612666150603130402
|View full text |Cite
|
Sign up to set email alerts
|

Rufinamide Improves Functional and Behavioral Deficits <i>via</i> Blockade of Tetrodotoxin-Resistant Sodium Channels in Diabetic Neuropathy

Abstract: Rufinamide is a structurally novel, antiepileptic drug approved for the treatment of Lennox-Gastaut syndrome. Its mechanism of action involves inhibition of voltage-gated Na+ channels (VGSCs) with possible membrane-stabilizing effects. VGSCs play a significant role in the pathogenesis of neuropathic pain. Therefore, we investigated the effects of rufinamide on tetrodotoxin-resistant sodium current (TTX-R I(Na)) in acutely dissociated rat dorsal root ganglion (DRG) neurons isolated from streptozotocin-induced d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Exact mechanism of action is still unknown, but in vitro studies suggest that it act through modulation of VGSC. It appears to prolong the inactive state of VGSC by slowing the recovery of these channels from inactivation (Wier et al, 2011; Kharatmal et al, 2015). VGSCs are key determinants regulating action potential generation and propagation; thus, changes in sodium channel function can have profound effects on neuronal excitability and pain signaling.…”
Section: Review Of Literature In Neuropathic Painmentioning
confidence: 99%
See 2 more Smart Citations
“…Exact mechanism of action is still unknown, but in vitro studies suggest that it act through modulation of VGSC. It appears to prolong the inactive state of VGSC by slowing the recovery of these channels from inactivation (Wier et al, 2011; Kharatmal et al, 2015). VGSCs are key determinants regulating action potential generation and propagation; thus, changes in sodium channel function can have profound effects on neuronal excitability and pain signaling.…”
Section: Review Of Literature In Neuropathic Painmentioning
confidence: 99%
“…TTX-sensitive includes (Nav1.3, Nav1.7) and TTX-resistant includes (Nav1.8, Nav1.9; Elliott and Elliott, 1993; Rush et al, 1998). Rufinamide has a great affinity for TTX-resistant than TTX-sensitive channels (Kharatmal et al, 2015). Rufinamide attenuates allodynia response in animal models of inflammatory and diabetes induced neuropathic pain (Suter et al, 2013; Kharatmal et al, 2015).…”
Section: Review Of Literature In Neuropathic Painmentioning
confidence: 99%
See 1 more Smart Citation
“…However, gain-of-function mutations in Nav 1.9 have been found to contribute to painful peripheral neuropathy [77, 78]. Additionally, researchers found Nav 1.9 to be involved with both acute and chronic inflammatory pain [79]. To demonstrate this, these researchers induced monoarthritis in mice via carrageenan injections.…”
Section: Voltage-gated Sodium Channel Pharmacologymentioning
confidence: 99%
“…Recently, Kharatmal et al [79] demonstrated that rufinamide decreases the activity of Nav 1.8 and 1.9 in a rat model of diabetic neuropathy. Blockage of these channels was observed to contribute to a decrease in both mechanical allodynia and thermal hyperalgesia in the study animals [79]. …”
Section: Voltage-gated Sodium Channel Pharmacologymentioning
confidence: 99%